Family Aggregation and Risk Factors for Breast Cancer in Affected Individuals - Julio Armando Sánchez Delgado; Nailé Edita Sánchez Lara (Revista Finlay)
Foundation: breast cancer is a systemic, multifactorial, polymorphic disease that develops in women with no family history of the disease. The possibility of family inheritance is described in 15-20 % of cases. Objective: to determine the family aggregation for breast cancer and the risk factors associated with this disease. Method: an analytical, retrospective, case-control type study was carried out, from individuals who attended the municipal genetic risk consultation located at the César Fornet Frutos University Polyclinic, Banes municipality, Holguín province in the period July-December 2019 aimed at verifying the existence or not of family aggregation of breast cancer. By simple random sampling, the sample consisting of 47 cases and 141 controls was obtained. The sample, consisting of 47 cases and 141 controls, was obtained by simple random sampling. The variables were: personal and family history of oncological disease, age, menarche, age at menopause, contraceptive pill ingestion, first child age of birth, breastfeeding, alcohol intake, smoking, family history. A questionnaire designed for the purposes of the study was applied. The Chi square calculation and Odds Ratio allowed estimating association between variables and the magnitude of association. Results: the age group of 60-69 years prevailed. The risk factors for smoking (OR = 4.1), ingestion of the contraceptive pill (OR = 3.1), and alcohol (OR = 2.8) had the highest association with the disease. A genetic counseling strategy was proposed based on the results. Conclusions: confluence of genetic and environmental factors determines family aggregation of breast cancer.